Phylogenetic relationships between Drosophila subobscura, D. guanche and D. madeirensis based on Southern analysis of heat shock genes. - Molto, M.D.; Martinez-Sebastian, M.J.; de Frutos, R. (Hereditas, 1994)
A Southern analysis of genomic DNA using Drosophila melanogaster probes for the major heat shock protein genes (Hsp82, Hsp70, Hsps encoding small proteins) was made to study the phylogenetic relationships between three Drosophila species belonging to the obscura group (D. subobscura, D. guanche, and D. madeirensis). The phylogenetic trees showed that D. madeirensis and D. subobscura are the most closely related species in the triad, while D. guanche is the most distantly related one. As in other Drosophila species, Hsp82 is a single copy gene in D. subobscura, D. guanche, and D. madeirensis, while Hsp70 and Hsps, which encode small proteins, are genic families. At least four sequences homologous to D. melanogaster Hsp70 were found in the obscura group species. These species have sequences which showed similarity with the four small Hsps of D. melanogaster.